Financial performance on share price: A study of listed Banks in Sri Lanka - Panuja, E. (University of Jaffna, 2020)
The main aim of the study is to examine the financial performance on share price, a study of listed banks in Sri Lanka over 2015 to 2019. The share Price of the bank was used as the dependent variable for the study while bank’s Financial performance as the independent variable which was measured through Return on Assets (ROA), Earning per share (EPS), Dividend per share (DPS) and Price earnings ratio (P/E ratio). Data was collected from 50 annual reports related to 10 Banks listed in the Colombo Stock Exchange for five years from 2015 to 2019. The researcher uses Descriptive and inferential analysis with the help of STATA's latest version. According to the correlation analysis, there is a positive relationship between the financial performance and the banks' share price. The findings of this study indicate that the Significant impact of Return on Assets, Earning per share, Dividend per share on share price, conversely insignificant impact Price-earnings ratio on the Share price in Banks in Sri Lanka.
Keywords: dividend per share; earning per share; price-earnings ratio; return on assets